2020
DOI: 10.3390/cancers12030534
|View full text |Cite
|
Sign up to set email alerts
|

Moving the Target on the Optimal Adjuvant Strategy for Resected Pancreatic Cancers: A Systematic Review with Meta-Analysis

Abstract: Combination regimens have shown superiority over single agents in the adjuvant treatment of resected pancreatic cancer (PC), but there are no data supporting definition of the best regimen. This work aimed to compare the efficacy and safety of mFOLFIRINOX, gemcitabine+capecitabine, and gemcitabine+nab/paclitaxel in PC patients. A meta-analysis was performed for direct comparison between trials comparing combination regimens and gemcitabine monotherapy. Subsequently, an indirect comparison was made between tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…The main treatment modality is surgery supplemented with chemotherapy and immune-targeted therapy; however, the resectability rate using surgery is only 15–20%, and adjuvant treatments show limited effects. Although, Studies have shown that nab-paclitaxel and mFOLFIRINOX (Oxaliplatin + Irinotecan+5-Fluorouracil + Calcium folinate) can effectively improve the survival rate of pancreatic cancer patients ( De Luca et al, 2018 ; Galvano et al, 2020 ). However, the overall 5-years survival rate of less than 8% ( Shaib et al, 2016 ; Ying et al, 2016 ; Mcguigan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main treatment modality is surgery supplemented with chemotherapy and immune-targeted therapy; however, the resectability rate using surgery is only 15–20%, and adjuvant treatments show limited effects. Although, Studies have shown that nab-paclitaxel and mFOLFIRINOX (Oxaliplatin + Irinotecan+5-Fluorouracil + Calcium folinate) can effectively improve the survival rate of pancreatic cancer patients ( De Luca et al, 2018 ; Galvano et al, 2020 ). However, the overall 5-years survival rate of less than 8% ( Shaib et al, 2016 ; Ying et al, 2016 ; Mcguigan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The deviations could be attributed to not including febrile neutropenia and sensory neuropathy in the study because of the lack of data in some of the trials. Through systematic reviews and meta-analyses performed by Galvano et al [4], Oneda and Zaniboni [26], and Kamarajah et al [7], FOLFIRINOX was found to be a superior adjuvant treatment option as compared to gem-nab/P or gem-cap for survival outcomes in resectable pancreatic cancer. The AE findings for resectable pancreatic cancer for this study were similar to that of Galvano et al [4] wherein grade 3/4 AE risk of FOLFIRINOX was higher compared to gem-cap and slightly lower compared to gem-nab/P [4].…”
Section: Discussionmentioning
confidence: 99%
“…There are no direct head-tohead trials comparing these chemotherapy treatments. Therefore, an indirect comparison was needed to assess superiority (i.e., efficacy and safety) of FOLFIRINOX compared to gemcitabine-based chemotherapy for both resectable and advanced pancreatic cancer [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] FOLFIRINOX (combination of 5 fluorouracil, leucov¬orin, oxaliplatin, and irinotecan) or gemcitabine with nabpaclitaxel (GemNab) are the recommended adjuvant chemotherapy regimens for pancreatic cancer. 9,10 In the phase 3 PRODIGE-24 study, patients diagnosed with pancreatic cancer who underwent R0 or R1 resection were randomized to either FOLFIRINOX or gemcitabine monotherapy and evaluated for disease-free survival (DFS), overall survival (OS), and toxicity. Results indicated significantly longer OS and DFS in patients treated with FOLFIRINOX vs gemcitabine (DFS: 21.6 months vs 12.8 months, hazard ratio [HR] = 0.58 [0.46-0.73]; OS: 54.4 months vs 35 months, HR = 0.64 [0.48-0.86]).…”
Section: What This Study Addsmentioning
confidence: 99%